2017
DOI: 10.1186/s12889-017-4440-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality in clusters of health-related behaviours in Europe: latent class analysis of a cross-sectional European survey

Abstract: BackgroundModifiable health-related behaviours tend to cluster among most vulnerable sectors of the population, particularly those at the bottom of the social hierarchy. This study aimed to identify the clusters of health-related behaviours in 27 European countries and to examine the socioeconomic inequalities in these clusters.MethodsData were from Eurobarometer 72.3–2009, a cross-sectional survey of 27 European countries. The analyses were conducted in 2016. The main sections of the survey included questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 38 publications
(46 reference statements)
5
35
0
3
Order By: Relevance
“…A better understanding of how sitting and sleep co-occur with diet, physical activity, alcohol consumption and smoking may assist in identifying populations who are at higher risk of poor health outcomes. Further, exploring how identified behavioral patterns vary by sociodemographic and psychological factors may add valuable context for the development and targeting of more efficacious health interventions and public health messaging 23,[37][38][39][40] . The primary aim of this study was to explore how diet quality, alcohol consumption, smoking status, physical activity, sitting time, and sleep quality, duration, and latency co-occur, and investigate the relationships between the identified behavioral patterns and mental and selfrated health.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A better understanding of how sitting and sleep co-occur with diet, physical activity, alcohol consumption and smoking may assist in identifying populations who are at higher risk of poor health outcomes. Further, exploring how identified behavioral patterns vary by sociodemographic and psychological factors may add valuable context for the development and targeting of more efficacious health interventions and public health messaging 23,[37][38][39][40] . The primary aim of this study was to explore how diet quality, alcohol consumption, smoking status, physical activity, sitting time, and sleep quality, duration, and latency co-occur, and investigate the relationships between the identified behavioral patterns and mental and selfrated health.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several studies have demonstrated an inverse relationship between unfavorable health-related behaviors and oral health in the context of socioeconomic disparities, 11,[14][15][16][17][18][19][20][21][22][23][24] which used various indicators for socioeconomic status such as the Index of Relative Socioeconomic Disadvantage (IRSD), 14 the poverty-income ratio, 15 and the Socioeconomic Disadvantage Index (SDI). 16 However, other studies have utilized household income 18 and/or head of household's social class.…”
mentioning
confidence: 99%
“…20 Various attempts to clarify the association between socioeconomic inequality and oral health related behaviors have also been made by clustering oral health behaviors. 23,24 To identify the socioeconomic disparities in dental behaviors that play an important role on oral health status, the authors of this study selected income and education factors that represent different dimensions of "causes of the causes" leading to oral health outcomes based on Andersen's behavioral models. 11,12 Each of the two variables as well as the combination of those components were utilized as independent variables.…”
mentioning
confidence: 99%
“…), longitudinálních studií (např. Kino et al, 2017) a dotazníkových šetření (Žmuk, 2015;Minicuci et al, 2016 aj.). Pro hodnocení zdraví, nemocnosti a úmrtnosti se používají jednak sekundární data národních a regionálních statistik, a dále se vychází z výběrových šetření, která se vztahují zejména k oblasti determinantů zdraví.…”
Section: úVodunclassified